Pengaruh Corporate Social Responsibility terhadap Penghindaran Pajak pada PT Wijaya Karya (Persero), Tbk - Sylviane Shinta Putri; Yeti Apriliawati (Indonesian Accounting Literacy Journal, 2020)
The large corporation seek to minimize taxes by tax avoidance. Tax avoidance can be said to reduce taxes by following existing regulations. This study aims to examine the effect of corporate social responsibility on tax avoidance at PT Wijaya Karya (Persero) Tbk. The independent variable in this study is corporate social responsibility while the dependent variable in this study is tax avoidance. The corporate social responsibility variable is measured by the GRI index while the tax avoidance variable is measured by the Effective Tax Rate (ETR). The analysis technique used in this research is simple linear regression analysis to test the effect of the independent variable on the dependent variable. Based on the test results of simple linear regression analysis, research shows that corporate social responsibility has a negative effect on tax avoidance at PT Wijaya Karya (Persero) Tbk.